Pengaruh Modal Usaha, Jam Kerja serta Unit Terjual terhadap Tingkat Pendapatan pelaku UMKM Sektor Perdagangan di Kecamatan Banjarsari, Kota Surakarta - Wikan Budi Utami; Eka Septina Sobriani; Darmanto Darmanto (Jurnal Akuntansi dan Pajak, 2023)
This study aims to determine the factors that influence the income of SMEs in the trade sector in Banjarsari District, Surakarta City. The independent variables in this study are working capital, working hours and units sold. While the dependent variable is the income of SMEs in the trading sector in Banjarsari District, Surakarta City. The sample used in this study were 69 SMEs in the trade sector in Banjarsari District, Surakarta City. Data was collected by distributing questionnaires to respondents. The analysis used is multiple regression analysis with SPSS version 28 program. The results of this study indicate that the three variables have a significant effect on the income of MSMEs in the trading sector in Banjarsari District, Surakarta City.